Análise do sistema logístico reverso de lâmpadas de iluminação pública do Sul Cearense - Brasil, Yllara Maria Gomes de Matos (2011)
This study aims to analyze the reverse flow of the bulbs used in street lighting in the southern region of Ceará state. These bulbs bring with them, as a key component to their operation, the heavy metal mercury, which is potentially damaging to the environment and human health, especially when converted, along with these same lamps, into post-consumer waste. The aspects covered in this study are: the steps of the reverse logistics system of used lamps carried out by the energy distribution company of Ceará, the assessment of the role of the agents who act upon the reverse flow of post-consumption bulbs used in street lighting of southern Ceará, the analysis of the advantages of the lamps decontamination carried out at the Logistics Center, located in Great Fortaleza, and the identification of needs for improvement in the system and consequent recommendations. Considering that recycling is the final most appropriate disposal of these used lamps from public lightening, the present study focuses on the reverse logistics, since this concept implies the rehabilitation of post-consumer products into the supply chain in order to reduce uncontrolled disposal and to encourage sustainable consumption. The methodology used in this research included a qualitative approach in the conduction of a case study whose data derived from direct observation and from the Electricity Distributor of Ceará. Although this study concludes that the waste management process from public lighting in southern Ceará is a reality and it complies with all the steps laid down in reverse logistics, it nevertheless notes that a considerable amount of post-consumption lamps, whether coming from the lighting of public or private spaces, still lies outside this system, thus not contributing to the adequate final disposal of the dangerous mercury.